Intra-individual comparison of gadolinium-enhanced MRI using pseudo-golden-angle radial acquisition with gadoxetic acid-enhanced MRI for diagnosis of HCCs using LI-RADS - Kim, Yoon Chul; Min, Ji Hye; Kim, Young Kon; Lee, Soon Jin; Ahn, Soohyun; Kim, Eunju; Peeters, Hans (European Radiology, 2019)
Objectives: To determine the usefulness of extracellular contrast agent (ECA)-enhanced multiphasic liver magnetic resonance imaging (MRI) using a pseudo-golden-angle radial acquisition scheme by intra-individual comparison with gadoxetic acid-MRI (EOB-MRI) with regard to image quality and the diagnosis of hepatocellular carcinoma (HCC). Materials and methods: This prospective study enrolled 15 patients with 18 HCCs who underwent EOB-MRI using a Cartesian approach and ECA-MRI using the pseudo-golden-angle radial acquisition scheme (free-breathing continuous data acquisition for 64 s following ECA injection, generating six images). Two reviewers evaluated the arterial and portal phases of each MRI for artifacts, organ sharpness, and conspicuity of intrahepatic vessels and the hepatic tumors. A Liver Imaging Reporting and Data System category was also assigned to each lesion. Results: There were no differences in the subjective image quality analysis between the arterial phases of two MRIs (p > 0.05). However, ghosting artifact was seen only in EOB-MRI (N = 3). Six HCCs showed different signal intensities in the arterial phase or portal phase between the two MRIs; five HCCs showed arterial hyperenhancement on ECA-MRI, but not on EOB-MRI. The capsule was observed in 15 HCCs on ECA-MRI and 6 HCCs on EOB-MRI. Five and one HCC were assigned as LR-5 and LR-4 with ECA-MRI and LR-4 and LR-3 with EOB-MRI, respectively. Conclusion: Free-breathing ECA-enhanced multiphasic liver MRI using a pseudo-golden-angle radial acquisition was more sensitive in detecting arterial hyperenhancement of HCC than conventional EOB-MRI, and the image quality was acceptable. Key Points: • The pseudo-golden-angle radial acquisition scheme can be applied to perform free-breathing multiphasic dynamic liver MRI. • Adopting the pseudo-golden-angle radial acquisition scheme can improve the detection of arterial enhancement of HCC. • The pseudo-golden-angle radial acquisition scheme enables motion-free liver MRI.
Keywords: Adult; Aged; Artifacts; Carcinoma, Hepatocellular; Contrast Media; Female; Gadolinium DTPA; Humans; Liver Neoplasms; Magnetic Resonance Imaging; Male; Middle Aged; Neoplasm Staging; Prospective Studies; Reproducibility of Results; ROC Curve; Artifacts; Carcinoma; Hepatocellular; Liver; Magnetic resonance imaging